PENGARUH PELATIHAN KERJA, LINGKUNGAN KERJA, BUDAYA KERJA TERHADAP KINERJA KARYAWAN PADA CV. TIRTA HAGUNA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Fitria, Anjar; Wahyuni, Ika; Soeliha, Siti (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
This study aims to determine the influence of job training, work environment, and work culture on employee performance at CV. Tirta Haguna, with job satisfaction as an intervening variable. The population for this study were employees at CV. Tirta Haguna. The sampling method was evenly distributed without considering the strata within the population. Data analysis and hypothesis testing were conducted using regression statistical methods. The results of the hypothesis test for direct influence using the Smart PLS 3.0 application show that job training has a positive but insignificant effect on job satisfaction, the work environment has a negative but insignificant effect on job satisfaction, work culture has a significant positive effect on job satisfaction, job training has a positive but insignificant effect on employee performance, work environment has a negative but insignificant effect on employee performance, work culture has a negative but insignificant effect on employee performance, job satisfaction has a significant positive effect on employee performance, job training has a significant positive but insignificant effect on job satisfaction through employee performance, work environment has a significant negative but insignificant effect on job satisfaction through employee performance, and work culture has a significant positive effect on job satisfaction through employee performance.